2007
DOI: 10.1002/cbdv.200790007
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Urease Inhibition, and Phytotoxic Studies of Binuclear Vanadium(IV) Complexes

Abstract: Vanadium plays an important role in biological systems and exhibits a variety of bioactivities. In an effort to uncover the chemistry and biochemistry of vanadium with nitrogen- and oxygen-containing ligands, we report herein the synthesis and spectroscopic characterization of vanadium(IV) complexes with hydrazide ligands. Substituents on these ligands exhibit systematic variations of electronic and steric factors. Elemental and spectral data indicate the presence of a dimeric unit with two vanadium(IV) ions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…The oxovanadium(IV) -ligand (1 : 1) complexes 1 -10 were synthesized by heating a mixture of the appropriate ligand and vanadyl sulfate in an equimolar ratio. The physical, analytical, and spectroscopic data of 1 -5 are collected in Table 1; those of 6 -10 have been reported previously [17] [18].…”
mentioning
confidence: 99%
“…The oxovanadium(IV) -ligand (1 : 1) complexes 1 -10 were synthesized by heating a mixture of the appropriate ligand and vanadyl sulfate in an equimolar ratio. The physical, analytical, and spectroscopic data of 1 -5 are collected in Table 1; those of 6 -10 have been reported previously [17] [18].…”
mentioning
confidence: 99%
“…Upon V(IV) complexation, the intense amide C=O band was shifted to a lower frequency, indicating coordination through the amide O-atom. All complexes exhibit strong V=O symmetric stretching absorptions around 981 ± 25 cm −1 , which are close to the V=O stretching frequency reported for other related oxovanadium(IV) complexes 31,[45][46][47][48] . These peaks are absent in parent ligands.…”
Section: Infrared Spectroscopymentioning
confidence: 51%
“…The product was dried in air. Physical and analytical data of oxovanadium complexes 1c-6c are given in Table 2, whereas those of 7c-11c are reported elsewhere 28,31 .…”
Section: Synthesis Of Hydrazide Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] It is notable that Ara and co-workers reported that some hydrazide ligands are inactive against urease, whereas their vanadium(IV) complexes show significant inhibitory potential against this enzyme and are found to be non-competitive inhibitors. 15 Aslam and co-workers reported that Schiff bases of hydrazone type also possess urease inhibitory activities. 16 Recently, our research group has reported some vanadium complexes with urease inhibitory activities.…”
Section: Introductionmentioning
confidence: 98%